National Security with a Canadian Twist: The Investment Canada Act and the New National Security Review Test - Subrata Bhattacharjee (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective discusses issues raised by the new national security test for proposed investments in Canada, including the ambiguity of the "national security" term and the possibility of politicized national security reviews. The author cautions the government not to adopt an over-expansive approach to the application of the new test. The Extended Note includes a detailed summary of these amendments to the Investment Canada Act and the recently published draft regulations that provide the details of the new national security review process.
Keywords: 330